Transition from Hydrocarbon Geopolitics to Critical Mineral Geopolitics - Ali Fuat Gökçe (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Geopolitical analysis considers factors beyond a state's geographical location, such as climate, topography, demographic structure, natural resources, country size, and technological advancement. In the 20th century, natural resource ownership and control became crucial to geopolitical analysis and policymaking. In recent years, the need for clean energy has become more prominent due to the negative effects of climate change. Developing technology and increasing populations have led to a greater demand for energy. Transformation is necessary to differentiate between energy systems that rely on clean technologies and hydro-carbon energy sources. This study will discuss the transition process from hydro-carbon energy to geopolitics based on critical minerals required for sustainable climate and clean energy, its reasons, and the current reflections of the future geopolitical struggle. Descriptive and historical research methods were used in this study. As a result of the study, it was determined that there may be changes in the geopolitical struggle depending on energy.